Comparative analysis of competitiveness and knowledge-technological network in two shrimp producing groups in Mexico - Carrazco-Escalante, José Crisóforo; Leyva-León, Eduardo; León-Balderrama, Jorge Inés (Iberoamerican Journal of Development Studies, 2021)
This study is to compare the knowledge-technological flow networks to the competitiveness in two shrimp producing groups from the municipality of Ahome (Sinaloa). It has focused on an analysis of social networks and the information was obtained by the application of a survey to a sample of 60 shrimp producing companies (7 belongs to Sinaloa Aquaculture Cluster and the 53 left belong to the social and private sector). It was found that in the Sinaloa Aquaculture Cluster the network indicators and the competitiveness scale were higher than the rest of the farms. This means that there is a greater transfer of information between the actors, and they also play a key role within the structure, as well as the limited size of the population in the organizations that make up the cluster shrimp farming as well as being focused on geographic and sectorial ambits. For that, is not possible to assume a causal relation and generalize the findings neither. Unity and strategic organization are key factors for this type of productive articulations, as they constitute an important source of social welfare and have a favorable impact on regional development.